Gambaran Pelaksanaan Toolbox Meeting dan Penggunaan Alat Pelindung Diri di Proyek Konstruksi Manggarai “Mainline I” Phase II Nindya Citra Kharisma KSO Jakarta Selatan - Ega Selpia Nurhayati; Siti Rukayah (Jurnal Persada Husada Indonesia, 2021)
Toolbox Meeting or Safety Talk is an informal meeting that focuses on occupational safety and health topics such as hazards in the workplace and how to work safely. The Safety Talk/Toolbox Meeting is usually short and takes place at the work location before the start of the work or work shift. This study aims to describe the implementation of the ToolBox Meeting and the use of personal protective equipment in the Manggarai "Mainline I" Phase II Construction Project of Nindya Citra Kharisma KSO South Jakarta. This study uses a qualitative research design. Qualitative methods are more based on phenomenological properties that prioritize appreciation (verstehen). The focus of the research is toolbox meetings (implementation methods) and the use of personal protective equipment (head protection, eye protection, ear protection, respiratory protection, hand protection, body protection, foot protection, safety protection). The sample in this study was using purposive sampling, and the number of samples was 4 informants. Data collection techniques using in-depth interviews, observation and document review methods. The results showed that most of the workers attended toolbox meetings and used personal protective equipment along with its functions and types. However, there are still workers who do not attend toolbox meetings and do not comply with the use of personal protective equipment. The recommendation in this research for the project is that a meeting is needed to evaluate the implementation of the toolbox meeting once a week where discussions are held by inviting representatives of the foreman workers to get information in the form of suggestions and criticisms that are useful for more effective and efficient toolbox meetings.